Motivasi Calon Pengantin Yang Menikah Usia Dini Di KUA Rasau Jaya - Silvia, Rita Silvia; Putri, Nur Aldina Eka; Kholifah, Eti Nur; Riyadi, Mohamad Dikta; ., Sartunah (BKI IAIN Pontianak, 2021)
Abstract: Early marriage is a marriage that is carried out by a couple, both male and female, who are under the minimum age of marriage based on marriage law, which under 19 years old both for men and woman. There are many reasons that causing them to choose married under age some of them caused by culture and religion, economic and educational level of the family. This study aims to determine the motivation of early married couples. In this research is using qualitative method and two bride. Collecting data by observation, interviews, and secondary data. Qualitative methods can make it easier for researchers to describe what the motivations of couples who want to marry underage are like. The results of the research taken on underage married couples show that there is no special motivation but of their own will who have agreed to marry underage and there are also those who follow the wishes of their parents to get married even though their age is not enough to following the law of marriage, which is in marriage law number 19 in 2019, the minimum age for marriage is 19 years, for both male and female. Abstrak: Pernikahan dini adalah pernikahan yang dilakukan oleh pasangan suami istri, baik laki-laki maupun perempuan, yang masih di bawah usia minimal perkawinan yang diatur dalam undang-undang perkawinan, yaitu 19 tahun bagi laki-laki dan 16 tahun bagi perempuan. Faktor penyebab pernikahan dini adalah budaya dan agama, tingkat ekonomi dan pendidikan keluarga. Penelitian ini bertujuan untuk mengetahui motivasi pasangan menikah dini. Penelitian ini merupakan penelitian kualitatif. Pengumpulan data dengan observasi, wawancara, dan data sekunder. Jumlah subjek berjumlah 2 orang. Metode kualitatif dapat memudahkan peneliti untuk mendeskripsikan seperti apa motivasi pasangan yang ingin menikah di bawah umur. Hasil penelitian yang dilakukan pada pasangan suami istri di bawah umur menunjukkan bahwa tidak ada motivasi khusus melainkan atas kemauan sendiri yang telah menyetujui untuk menikah di bawah umur dan ada juga yang menuruti keinginan orang tuanya untuk menikah walaupun usianya tidak mencukupi. yang diatur dalam undang-undang. perkawinan dalam UU no. 19 Tahun 2019, usia minimal untuk menikah adalah 19 tahun, baik pria maupun wanita.